Tracking parallel adaptation of shell morphology through geological times in the land snail genus Pupilla (Gastropoda: Stylommatophora: Pupillidae). Issue 3 (23rd June 2020) - Haase, Martin; Meng, Stefan; Horsák, Michal
Abstract: Changing environmental conditions force species either to disperse or to adapt locally either genetically or via phenotypic plasticity. Although limits of plasticity can be experimentally tested, the predictability of genetic adaptation is restricted due to its stochastic nature. Nevertheless, our understanding of evolutionary adaptation has been improving in particular through studies of parallel adaptation. Based on molecular phylogenetic inferences and morphological investigations of both recent and fossil shells we tracked the morphological changes in three land snails, Pupilla alpicola, Pupilla loessica and Pupilla muscorum . These species differ in habitat requirements as well as historical and extant distributions with P. alpicola and P. loessica being more similar to each other than to P. muscorum . Therefore, we hypothesized, that the three species reacted independently and individually to the conditions changing throughout the Pleistocene, but expected that changes within P. alpicola and P. loessica would be more similar compared to P. muscorum . Indeed, intraspecific shell shape differences across time were similar in P. alpicola and P. loessica, suggesting that similar niche shifts have led to similar transformations in parallel. In contrast, extant P. muscorum populations were practically identical in shape to their ancestors. They have probably tracked their ecological niches through time.